Kinetic and Thermodynamic Studies of the Oxidation of Eugenol and Isoeugenol by Sodium N-Chlorobenzene-p-Sulphonamide in NaOH - Prabhu, D.V.; Tandel, M.A.; Parbat, H.A. (Asian Journal of Chemistry, 2011)
Eugeneol and isoeugenol are used in the perfume and fragrance industry. The oxidation of these alcohols has been carried out using sodium N-chlorobenzene-p-sulphonamide in NaOH medium. The oxidation was studied using pseudo first order kinetics with respect to the N-haloamine oxidant. Aliquots of the reaction mixture were withdrawn at regular time intervals, the reaction was quenched and the unreacted oxidant was estimated iodometrically. The pseudo first order rate constants were determined from the straight line graphs of log(a-x) versus time. The variation of oxidation rate with substrate and oxidant concentrations and ionic strength was studied. Potassium sulfate was used to study the effect of ionic strength (μ) on oxidation rate in accordance with the Bronsted-Bjerrum equation, log k= log k0 +1.02 ZAZB √μ. The oxidation rate was found to be independent of ionic strength. From the temperature dependence of reaction rate, the energy of activation and other thermodynamic activation parameters were evaluated. The rate determining step of the oxidation process has been identified and suitable reaction mechanisms and rate laws have been discussed. The oxidation rates follow the sequence: isoeugenol > eugenol, which has been explained on the basis of the structures and steric factors of the substrates under investigation.